2017
DOI: 10.1136/bmj.j1284
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic pain using complementary and integrative medicine

Abstract: Complementary and integrative medicine (CIM) encompasses both Western-style medicine and complementary health approaches as a new combined approach to treat a variety of clinical conditions. Chronic pain is the leading indication for use of CIM, and about 33% of adults and 12% of children in the US have used it in this context. Although advances have been made in treatments for chronic pain, it remains inadequately controlled for many people. Adverse effects and complications of analgesic drugs, such as addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 82 publications
1
64
0
Order By: Relevance
“…Complementary and integrative medicine including acupuncture, dietary supplements, and mind-body systems are being increasingly used for treating chronic pain partly to reduce complications of longterm opioid use. 95 We found that electro-acupuncture without anesthesia in awake BERK sickle mice led to a variable analgesic response, categorized into high, moderate, and low responses. 96 These effects were correlative to a reduction in inflammatory cytokines, SP, and neurogenic inflammation in the periphery and signaling pathways of nociception in the spinal cord, thus influencing the sickle microenvironment as well as nociception centrally.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 88%
“…Complementary and integrative medicine including acupuncture, dietary supplements, and mind-body systems are being increasingly used for treating chronic pain partly to reduce complications of longterm opioid use. 95 We found that electro-acupuncture without anesthesia in awake BERK sickle mice led to a variable analgesic response, categorized into high, moderate, and low responses. 96 These effects were correlative to a reduction in inflammatory cytokines, SP, and neurogenic inflammation in the periphery and signaling pathways of nociception in the spinal cord, thus influencing the sickle microenvironment as well as nociception centrally.…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 88%
“…The top 4 CMs most often perceived as being useful were also the most recommended (Osteopathic treatment, acupuncture, yoga, and therapeutic massage). Interestingly, all four CM treatments have shown some effect in the treatment of chronic or recurrent LBP [ 9 , 14 , 16 ]. These treatments, among others, were already recommended in the ACP’s 2007 guidelines as second-line treatments [ 18 ] and appear in the 2017 guidelines as first-line options [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines CM as “a broad set of health care practices that are not part of that country’s own tradition or conventional medicine and are not fully integrated into the dominant health-care system”. Some studies suggest that CM non-pharmacologic therapies such as acupuncture [ 7 9 ], yoga [ 10 , 11 ], Tai-Chi [ 12 ], Mindfulness-based stress reduction [ 13 ], osteopathy [ 14 ] and hypnosis [ 15 ] might be useful treatment options for patients suffering from chronic LBP [ 16 ], although more studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence does not substantiate that the choice of needle points or the type of acupuncture affects efficacy, but more sessions and more needle applications are associated with more favourable outcomes in adults [ 15 ]. Acupuncture is considered safe when offered by trained practitioners, both when used in adults [ 13 , 16 ] and in children [ 17 ]. Acupuncture for children has gained some acceptance in Western medicine, even though the evidence supporting the use of acupuncture in small children is sparse [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%